Akuntabilitas dan Inklusivitas Dana Sosial Vihara Avalokitesvara di Madura: Perspektif ISAK 335 - Moh Hakamil Ali Kamil; Moch Cholid Wardi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The role of houses of worship as drivers of social change through public funds has become increasingly crucial. Vihara Avalokitesvara in Madura presents a compelling case study; as a symbol of tolerance, it stands within a predominantly Muslim settlement in Polagan Village. This research aims to analyze the accountability and inclusivity of social funds at Vihara Avalokitesvara from the perspective of PSAK 101, while examining how leadership transitions have influenced social relations in Polagan Village. Although the management conducts routine monthly recording, these records remain restricted to internal use and lack transparency toward the public. This creates a gap between formal regulations (PSAK 101) and field practices. Utilizing a descriptive qualitative method, this study gathers data through in-depth interviews and physical field observations. The findings reveal that minimal transparency does not diminish the trust of the Polagan Village community. This phenomenon occurs because the community prioritizes tangible benefits such as road repairs and access to clean water over rigid administrative reports. Consequently, the researcher proposes the concept of